Impact of integrating pharmacists into primary care teams on health systems indicators: a systematic review - Hayhoe,B; Acuyo,Cespedes J; Foley,K; Majeed,F; Ruzangi,J; Greenfield,G (British Journal of General Practice, 2019)
Background: Evidence suggests that pharmacists integrated in primary care can improve patient outcomes and satisfaction, but their impact on healthcare systems is unclear. Aim: To identify key impacts of integration of pharmacists in primary care on health system indicators such as healthcare utilisation and costs.Design and setting: A systematic review of literature.Method: We examined EMBASE, MEDLINE, SCOPUS, HMIC, CINAHL and CENTRAL, and reference lists of relevant studies. RCTs and observational studies were included, published up to June 2018, which considered health system outcomes of integration of pharmacists in primary care. Risk of bias assessment used the Cochrane Risk of Bias Quality Assessment tool for RCTs, and the NIH National Heart, Lung and Blood Institute quality assessment tool for observational studies. Data were extracted from published reports and findings synthesized.Results: Searches identified 3,058 studies; 28 met the inclusion criteria. Most included studies were of fair quality. Pharmacists in primary care resulted in reduced use of GP appointments and reduced emergency department attendance, but increased overall primary care use. There was no impact on hospitalisations, but some evidence of savings in overall health system costs and medication costs.Conclusion: Integration of pharmacists in primary care may reduce GP workload, as well emergency department use. Further higher quality studies are needed, including research to clarify cost-effectiveness and long-term impact on health system outcomes.